The effect of 8 MeV electron beam irradiation on the structural, optical and photoluminescence properties of ZnS thin films. Issue 2 (1st February 2019) - Priya, K.; Rao, Gowrish K.; Ashith, V.K.; Sanjeev, Ganesh; Verma, Vijay Pal; Petwal, Vikash Chandra; Dwivedi, Jishnu
Abstract: The thermal deposited ZnS thin films with thickness ranging from 400 nm to 1000 nm were irradiated with various doses of 8 MeV electrons. The structural, optical and photoluminescence properties of the irradiated films were studied in detail. The films with thickness ranging from 600 nm to 650 nm were found to have highest tolerance to irradiation. The crystallite size of these films increased after irradiation. The irradiated films were also found to have high absorption in the UV region and their bandgap showed only marginal variation of 2.57%. The photoluminescence spectra of the films were unaffected by irradiation, confirming the stability of their energy band structure. Thus, the thermal deposited ZnS films were found to be highly suitable for UV photo-detection in the radiation environment.